Mācītāja Vladimira Molčanova teoloģiskie uzskati: reliģisko identitāšu pārklāšanās piemērs Latvijas baptismā 20. gs - Pallo, Uģis (Latvijas Universitāte, 2020)
Maģistra darba tēma ir: “Mācītāja Vladimira Molčanova teoloģiskie uzskati: reliģisko identitāšu pārklāšanās piemērs Latvijas baptismā 20. gs”. Šis darbs ir pētījums baptismam Latvijā. Lai būtu iespējami vieglāk izprast Latvijas kontekstu, pavisam nedaudz tiek apskatīts vēsturiskais šīs denominācijas attīstības ceļš. Šī darba galvenais pētījums ietver mācītāja V. Molčanova dzīves gaitu, sprediķu analīzi un viņa reliģisko identitāšu pārklāšanās piemēru un personību Latvijas baptismā. Darbs atspoguļo publicētu, arhīvu un periodikas, kā arī nepublicētu materiālu saturu. Šajā darbā iekļauto sprediķu citāti atspoguļo Kesvikas svētošanas kustības teoloģisko domu. Darbs norāda uz bijušo un esošo iekšējo spriedzi pašā Latvijas baptismā.

The topic of the master's thesis is: "Theological views of Pastor Vladimir Molchanov: an example of overlapping religious identities in Latvian Baptism in the 20th century". This work is a research of baptism in Latvia. In order to make it as easy as possible to understand the Latvian context, the historical development path of this denomination is considered very little. The main research of this work includes the course of Pastor V. Molchanov's life, the analysis of sermons and the study of the overlap of his religious identities and his personality in Latvian Baptism. The work reflects the content of published, archival and periodicals, as well as unpublished materials. The quotations from the sermons included in this work reflect the theological idea of the Keswick Holyness movement. The work also reflects the internal tension in Latvian Baptism itself.
Theological views of Pastor Vladimir Molchanov: an example of overlapping religious identities in Latvian Baptism in the 20th century
Keywords: Teoloģija un reliģiju zinātne; Baptisms; baptisti Latvijā; Vladimirs Molčanovs; multikonfesionalisms; svētošanas kustība